Spongy moths from Europe and Asia: Who could have higher invasion risk in North American? - Yi Luo; Changxi Li; Xiaokang Hu; Jianmeng Feng (PLoS ONE, 2025)
North American forest systems are significantly impacted by spongy moths (Lymantria dispar Linnaeus). It is unclear, nevertheless, how are the invasion risks of spongy moths from Asia and Europe in North American relative to each other. In this study, we compared the potential ranges of spongy moths from Asia (ASM) and those from Europe (ESM) in North America, and investigated the range shifts between spongy moths in North America (NASM) and ASM and ESM. ASM and ESM would occupy larger potential ranges in North America than NASM, i.e., 7.16 and 6.98 times, respectively. Thus, one should not undervalue the invasive potential posed by spongy moths from Asia and Europe. Compared to ESM, ASM displayed larger ranges in North America. It is likely due to ASM’s tolerance of more variable climates. Consequently, even though ASM was more recently introduced to North America than ESM, it’s possible that the former has higher invasion risk in North American.